Evaluation of Leadership and Personnel Management on Work Effectiveness at the Jakarta Customs and Excise Regional Office - Rusman Hadi; Zulkifli Rangkuti; Nurwulan Kusuma Devi (Dinasti Publisher, 2026)
This study aims to determine the influence of leadership on employee work effectiveness, to determine the influence of employee management on employee work effectiveness, to determine the influence of leadership and employee management together on work effectiveness, the calculated t value for the Leadership variable (X1 ) is 9.773 while the t table value for N = 100 is 1.983 . So 9.773 > 1.983 , then H0 is rejected and Ha is accepted, it can be stated that Leadership (X1 ) has a significant effect on Employee Work Effectiveness (Y), the calculated t value for the Employee Management variable ( X2) is 10.755 , while the t table value for N = 100 is 1.983 . So 10.755 > 1.983 , then H0 is rejected and Ha is accepted, it can be concluded that partially the Employee Management variable (X2) has an effect on Employee Work Effectiveness (Y), the results test ANOVA obtained a calculated F value of 390,320. While the F table ( 0.05) for N = 100 is 2.70 . So the calculated F > from the F table ( 0.05) or 390,320 > 2.70 with a significant level of 0.000 because 0.000 <0.05, it can be said that Leadership ( X1 ) and Personnel Management (X2) together have a positive effect on Employee Work Effectiveness (Y)